Vegetarian or gluten‐free diets in patients with inflammatory bowel disease are associated with lower psychological well‐being and a different gut microbiota, but no beneficial effects on the course of the disease. Issue 6 (1st July 2019) - Schreiner, Philipp; Yilmaz, Bahtiyar; Rossel, Jean-Benoît; Franc, Yannick; Misselwitz, Benjamin; Scharl, Michael; Zeitz, Jonas; Frei, Pascal; Greuter, Thomas; Vavricka, Stephan R; Pittet, Valérie; Siebenhüner, Alexander; et al.
Abstract : Background: Many inflammatory bowel disease (IBD) patients follow a restrictive diet due to perceived positive effects on their symptoms. We assessed the prevalence of vegetarian (VD) and gluten‐free diets (GFDs) in IBD patients, the reasons for following such a diet, and whether nutrition has an impact on disease activity and microbiota composition. Methods: We included 1254 patients from the Swiss Inflammatory Bowel Disease Cohort Study with prospective acquisition of clinical data and psychosocial, disease‐related and lifestyle factors between 2006 and 2015. Dietary habits were assessed through a self‐report questionnaire. In 92 patients, we analysed intestinal mucosa‐associated microbial composition using high‐throughput sequencing. Results: Overall, 4.1% ( n = 52) of the patients reported following a VD and 4.7% ( n = 54) a GFD. No differences regarding disease activity, fistula, hospitalization or surgery rates were observed. Patients on a VD or GFD had significantly higher levels of post‐traumatic stress symptoms. Furthermore, GFD patients had significantly higher anxiety and depression symptom levels. The gut microbiota composition in IBD patients following a VD or GFD was significantly different compared to that of omnivores. Conclusions: Although we did not identify a relevant impact of a specific diet on the course of the disease, there was a significant association with lower psychological well‐being in VD and GFD patients.